2021
DOI: 10.1055/a-1704-3086
|View full text |Cite
|
Sign up to set email alerts
|

Sport Supplements and the Athlete’s Gut: A Review

Abstract: Vigorous or prolonged exercise poses a challenge to gastrointestinal system functioning and is associated with digestive symptoms. This narrative review addresses 1) the potential of dietary supplements to enhance gut function and reduce exercise-associated gastrointestinal symptoms and 2) strategies for reducing gastrointestinal-related side effects resulting from popular sports supplements. Several supplements, including probiotics, glutamine, and bovine colostrum, have been shown to reduce markers of gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…It is well recognized that gastrointestinal (GI) symptoms are prevalent among individuals partaking in endurance exercise, although estimates vary with factors such as exercise intensity, age, sex, training experience, nutritional intake, supplement use, and psychological state. [1][2][3][4][5] Using a prospective design, Wilson 6 found that male and female runners experienced at least one GI symptom on 84% and 78% of their runs, respectively, over a 30-day period, and moderate-to-severe symptoms ($5 on a 0-10-scale) were experienced on 14% to 22% of runs. Competition-related GI symptoms are also commonplace, with $90% of ultra-endurance race (100-mile runs, 70.3-mile triathlons, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that gastrointestinal (GI) symptoms are prevalent among individuals partaking in endurance exercise, although estimates vary with factors such as exercise intensity, age, sex, training experience, nutritional intake, supplement use, and psychological state. [1][2][3][4][5] Using a prospective design, Wilson 6 found that male and female runners experienced at least one GI symptom on 84% and 78% of their runs, respectively, over a 30-day period, and moderate-to-severe symptoms ($5 on a 0-10-scale) were experienced on 14% to 22% of runs. Competition-related GI symptoms are also commonplace, with $90% of ultra-endurance race (100-mile runs, 70.3-mile triathlons, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…), we observed a hypoactivity in the conversion from LA to DGLA. Moreover, this deficit might be connected to an alteration of the immune system [ 58 , 59 ] and intestinal health, including intestinal permeability, expected to be disrupted when increasing training loads [ 60 ], which in turn is related to the inflammatory status [ 61 ] as explained previously, being DGLA a precursor of AA.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that NaHCO 3 at doses over 0.2 g/kg b.w. can acutely trigger adverse gastrointestinal symptoms [ 30 ]. These symptoms include diarrhea, which not only leads to dehydration but also microbiota disturbances.…”
Section: Aerobic Exercise—diet and Supplementsmentioning
confidence: 99%